Neuromuscular and metabolic responses of the pre-exhaustion method in highly-trained individuals - Pinto Silva, G.; Pereira Guimarães, M.; Costa Campos, Y. A.; Costa Moreira, O.; Fernandes da Silva, S. (Journal of Human Sport & Exercise, 2019)
Several studies investigated the pre-exhaustion resistance training (PERT), no study investigated the responses after the pre-fatigue of two auxiliary muscles. The purpose of this study was to evaluate the neuromuscular and metabolic effects of PERT in highly-trained individuals. Twenty-one men (24.90 ± 4.54 years) who were experienced in resistance training were randomly distributed into two groups. In the conventional resistance training (CRT), three sets of each exercise were performed separately (front raise [FR], triceps-forehead [TF] extensions, and bench press [BP]), with an interval of 45 seconds between the sets. In the PERT method, the exercises were performed in sequence (FR, TF, and BP), with an interval of 2 minutes 15 seconds between the sets. The electromyography (EMG), signal was acquired during the execution of the FR, TF, and BP exercises, and the muscles anterior deltoid, triceps brachii long head, and pectoralis major (clavicular head and sternal head). Lactate levels were measured before workout and at the end of each set in each method. There was no difference in the EMG activation of PMC and PMS muscles when compared to the PERT and CRT methods. Clavicular portion, PERT/CRT: 1st 42.1±7.1/42.1±6.6µV, 2st 45.9±5.5/43.5±6.2 µV, 3rd 45.5±5.7/43.9±6.1µV. Sternal portion, PERT/CRT: 1st 36.2±9/35±5.7µV, 2st 38.3±8.9/35.3±6µV, 3rd 36.8±7.1/35.1±5.1µV. However, lactate accumulation was significantly higher in PERT when compared CRT. PERT/CRT 1st 7.6.0±1.8/5.7±1.5 mmol/l; 2st: 9.5±1.5/8.4±2 mmol/l; 3rd:10.0±2.1/9.4±1.8 mmol/l, when compared to CRT. The PERT was more effective, producing greater metabolic stress, demonstrating to be a high-intensity method that leads to muscle adaptation.